Infant feeding practices in the first 24–48 h of life in healthy term infants. (22nd April 2013) - Johns, HM; Forster, DA; Amir, LH; Moorhead, AM; McEgan, KM; McLachlan, HL
Abstract Aim To examine in‐hospital infant feeding practices, focusing on initiation and prevalence of breastmilk expression and to describe the proportion of women having a breast pump immediately after birth. Methods Postpartum women were recruited from three hospitals in Melbourne, Australia, between 2009 and 2011. Inclusion criteria: having had a healthy singleton term infant, intending to breastfeed and fluency in English. Data were collected using a structured questionnaire. Results Just over 1000 women were recruited at 24–48 h postpartum; 50% were primiparous. Forty‐seven per cent of infants had been fully breastfeeding at the breast from birth, and another 47% had received at least some expressed breastmilk. Forty per cent of first‐time mothers reported having had a problem breastfeeding, and 46% already had a breast pump prior to the birth of their infant. Conclusions Early breastfeeding problems were common, and less than half the infants had fed only at the breast in the first days of life. Given the normalization of breastmilk expression, more evidence is needed regarding the impact of expressing on duration of breastmilk feeding and maternal health outcomes.